Visceral Fat Dysfunctions in the Rat Social Isolation Model of Psychosis - Stefania Schiavone; Giulia M. Camerino; Emanuela Mhillaj; Margherita Zotti; Marilena Colaianna; Angelo De Giorgi; Antonello Trotta; Francesco P. Cantatore; Elena Conte; Maria Bove; Paolo Tucci; Maria G. Morgese; et al. (Frontiers Media S.A., 2017)
Medication with neuroleptics has been associated with adipose tissue dysfunctions and, in particular, with increased visceral fat amount. However, several studies suggested that antipsychotic treatment might not be the main responsible of fat mass accumulation, as this has been also described in not treated psychotic patients. One of the most used "drug-free" rodent models of psychosis is the social isolation rearing of young adult rats, which provides a non-pharmacologic method of inducing long-term alterations reminiscent of symptoms seen in psychotic patients. Recent data highlighted a crucial role of redox imbalance in adipose tissue dysfunctions, in terms of decreased antioxidant defense and increased reactive oxygen species (ROS). Here, we investigated possible oxidative stress-related biomolecular alterations associated with visceral fat increase in 7 week isolated rats. To this purpose, we quantified total and visceral fat amount by using dual-energy X-ray (DEXA) absorptiometry. On visceral fat, we analyzed the expression of specific ROS-producer genes (Nox1, Nox4, Hmox-1), antioxidant enzymes (Prdx1 and Ucp-1) and oxidative stress-induced damage markers (Cidea, Slc2a4, and Acacb). The impact of oxidative stress on beta3-adrenergic receptors (Adrb3), at both mRNA and protein level, was also assessed. We found that 7 weeks of social isolation induced an increase in total and visceral fat, associated with a decrease in Prdx1 (mRNA and protein) as well as Ucp-1 mRNA levels and an enhanced expression of Nox1 (mRNA and protein) and Hmox-1 mRNA. No differences were detected in Nox4 mRNA levels between grouped and isolated animals. Elevations in Cidea, Slc2a4, and Acacb expression in visceral fat of isolated animals accounted for oxidative stress-related damage in this tissue, further associated with a significant increase in Adrb3 mRNA and protein. Our results provide a novel understanding of the pathological link existing among psychosocial stress-induced psychosis, adipose tissue dysfunctions and redox imbalance, opening new therapeutic perspectives for the treatment of alterations in peripheral tissues associated with this mental disorder.